Foliar spraying with silicon in the yield and health of soybean cultivars (Revista de Ciências Agroveterinárias, 2019)
Soybean is one of the main agricultural species cultivated in Brazil, but it may have reduced yield due to the incidence of pests and diseases. This study aimed to evaluate the effect of silicon spray at different soybean phenological stages on the severity of Asian rust (AR), the soybean caterpillar population, and the yield of soybean. The experiment was conducted in the 2012/2013 crop season through a randomized complete block with five replications and factorial scheme (2x5). The factors were two soybean cultivars (Anta 82 RR and CD 2737 RR) and five treatments for AR management (T1- negative control; T2- aluminum silicate in R1 + R4; T3- aluminum silicate in V5 + R1 + R4; T4- aluminum silicate in V5 + R1 + R4 + R5.1; and T5- positive control: trifloxystrobin + prothioconazole in R1 + R4). Defoliation, disease severity, area under the disease progress curve (AUDPC) and yield were evaluated. Soybean caterpillar population was monitored weekly using a beating sheet. Sprays of aluminum silicate reduced the severity of AR and AUDPC in relation to the control, but it was less effective than the positive control. Grain yield increased when three and four aluminum silicate sprays were performed, and the population level of soybean caterpillars was not reduced by silicon.
Keywords: Aluminum silicate; Phakopsora pachyrhizi; Anticarsia gemmatalis; Chrysodeixis includens